IMPLEMENTASI TARGET COSTING DALAM UPAYA EFISIENSI BIAYA PRODUKSI UNTUK MENINGKATKAN LABA PRODUK - Mediaty, Mediaty; Usman, Asri; Pratiwi, Dwi Dian; Nurul Amalia, Lestari Rezki; Wijayanti, Winola (Transpublika Publisher, 2024)
This paper looks into how MIE NAGA figures out their production costs, checking if Target Costing makes a difference in cutting costs, and seeing how using Target Costing can help boost their product profits. This research is a type of qualitative research using a case study approach. The type of research used is qualitative with a case study model. Data sources refer to primary data and secondary data. Data analysis and processing used to get answers to the formulation of the problem is to get supporting data and then processed with the target costing method used until the end of the problem. In essence, the application of the target costing method is effective for streamlining production costs. this is evident that the difference from the total production cost in 2020 and the total production cost in 2021 before and after the application of the target costing method is Rp. 340,206,650, and the total production cost is Rp. 516,244,150 and Rp. 176,037,500. Furthermore, there is an increase in product profit in the amount of the difference in revenue seen from 2020 and 2021 by 71.4%. Meanwhile, two additional alternatives that have been implemented through the value engineering method are changes in selling prices to maximize profits.